2021
DOI: 10.22575/interventionalradiology.2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Supraduodenal and Right Gastric Arteries Originating from A Common Trunk: A Rare Anatomical Variant

Abstract: Knowledge of the anatomic variations of the supraduodenal artery (SDA) and right gastric artery (RGA) is necessary to reduce the procedure time and radiation exposure dose, as well as to avoid unexpected complications of catheter placement before hepatic arterial infusion chemotherapy. The SDA and RGA most commonly arise from the gastroduodenal artery (GDA) and the proper hepatic artery, respectively; however, they can branch from the left hepatic artery (LHA). In addition, the SDA frequently anastomoses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Starting with the CT, numerous studies have shown variations in the origin and branching patterns of its subsequent branches. Typically, the CT splits into the common hepatic artery, splenic artery, and left gastric arteries from the abdominal aorta [ 7 ]. While an individual may possess a conventionally trifurcated CT, the branching patterns of its derivatives can often be atypical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting with the CT, numerous studies have shown variations in the origin and branching patterns of its subsequent branches. Typically, the CT splits into the common hepatic artery, splenic artery, and left gastric arteries from the abdominal aorta [ 7 ]. While an individual may possess a conventionally trifurcated CT, the branching patterns of its derivatives can often be atypical.…”
Section: Discussionmentioning
confidence: 99%
“…The right hepatic artery then gives the origin of the cystic artery as a single stem from the right and posterior to the hepatic duct within Calot’s triangle and supplies the gallbladder [ 3 , 6 ]. It has been reported that apart from the proper hepatic artery, the right gastric artery also originates as a common trunk of the supraduodenal artery from the gastroduodenal artery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%